The first data on species diversity of leeches (Hirudinea) in the Irtysh River Basin, East Kazakhstan - Kaygorodova, Irina A.; Fedorova, Lyudmila I. (Zootaxa, 2016)
The Irtysh River is one of the major waterways of the Republic of Kazakhstan. The river originates in the territory of Mongolia and China, flows through the East Kazakhstan and falls into the Ob River in the Western Siberia of Russia. The Kazakhstan section of the river, with length of 1698 km and water resources about 43.8 km3 (Dyusebaeva 2012), is situated on the border of the West Siberian Plain, the Altai Mountains and the Kazakh Uplands. As the river crosses various natural zones, characteristics of its hydrological regime is very diverse. In the south, in the area of Ust-Kamenogorsk, the valley of the Irtysh extends. In the upper reaches up to the city of Semey (formerly Semipalatinsk), the river is surrounded by plain and mountain landscapes. Downstream from Semey, the Irtysh enters the West Siberian Plain and flows to north-west through dry steppes. The riverbed is unstable: sometimes it is very tortuous, sometimes it is broken into branches, and, there are a lot of sand spits. The hydrological level of the Kazakhstan part of the Irtysh River is regulated with the cascade of storage reservoirs near the towns Bukhtarma, Ust-Kamenogorsk and Shulbinsk.